Prevalence of Self-Medication with Antibiotics in Europe: A Scoping Review - Stanislav Gueorguiev; Hristina Lebanova; Svetoslav Stoev; Nadia Veleva; Simona Belcheva; Vasil Madzharov (Journal of Biomedical & Clinical Research, 2023)
The most common cause of antibiotic resistance is the irrational use of antibiotics. Most of the irrational use of antibiotics is related to use in the community and the prevalence of self-medication in different populations. This review aimed to explore the prevalence of self-medication with antibiotics in European countries and the main sources of antibiotics. An online search of Pubmed and Scopus was conducted to identify relevant studies. A two-phase mapping approach was used. All steps in this scoping review were carried out using the Covidence® software. A total of 22 studies were included. The prevalence of self-medication with antibiotics is greater in Southern European countries than in Northern and Western European countries. The main sources of over-the-counter antibiotics are community pharmacies and leftovers from previous courses. Targeted communication strategies and interventions are needed to reduce the overuse of antibiotics and to slow down the spread of antibiotic resistance until new classes of effective antibiotics are developed.